Trans-European component of the european information space - Тихомирова, Євгенія Борисівна; Tykhomyrova, Yevheniia B. (Київський національний університет імені Тараса Шевченка, Інститут міжнародних відносин, 2013)
The article is devoted to the nature and structure of the trans-European information space. Particular attention is paid to the development of the trans-European information space which includes the processes of the structure and subjects’ formation of the information activity of the trans-European standard. According to the author, the creation of the European information space helps to overcome the traditional dispositions of the countries and regions and also to provide systematical co-operation of the subjects of the information life. У статті розглядається сутність та структура транс’європейського інформаційного простору. Особливу увагу автор приділяє аналізу процесів формування структур та суб’єктів інформаційної діяльності загальноєвропейського масштабу. На думку автора, формування транс’європейського інформаційного простору сприяє подоланню диспозицій країн і регіонів та забезпечує системну взаємодію суб’єктів інформаційного життя.
Транс'європейська складова європейського інформаційного простору
Keywords: європейський інформаційний простір; транс'європейський простір; Європейський Союз; Рада Європи; НАТО; ОБСЄ; European information space; trans-European space; the European Union; the Council of Europe; NATO; the OSCE